Judges' perceptions of expert reports: The effect of neuroscience evidence. (November 2018) - Moulin, Valerie; Mouchet, Caroline; Pillonel, Tessa; Gkotsi, G.-M.; Baertschi, Bernard; Gasser, Jacques; Testé, Benoit
Abstract: This article explores the impact of neuroscience evidence on how expert reports are perceived and their effects on the decisions made by trial judges. Experimental psychology has demonstrated a number of cognitive effects arising from exposure to neuroimaging data which may bias judgments and lead to (mis)interpretations that can affect decisions. We conducted a study on a sample of 62 Swiss and French judges in order to determine whether their perceptions of the credibility, quality and scientific basis of a psychiatric evaluation of a criminal defendant vary according to whether or not the evaluation includes neuroscientific data. Quantitative analyses were conducted in order to evaluate significant differences between the two conditions (one-way analyses of variance) and moderation and conditional analyses to examine whether the participants' sex and length of professional experience moderated the effect of the conditions. Terminological and thematic analyses were carried out on open questions. Quantitative and qualitative results suggest that the presence of neuroscience data in an expert report affects judges' perceptions of the quality, credibility, and scientificity (reliability, objectivity, scientific basis) of the report, and the persuasiveness of the evidence it provided. Moreover, this phenomenon was stronger in more experienced judges than in less experienced judges.